Jack and Jill Be Nimble: A Historical Analysis of an "Adless" Children's Magazine. Issue 4 (2nd October 2018) - Holiday, Steven
Abstract : The children's magazine Jack and Jill is commonly perceived to have been "adless" from its first issue in 1938 until 1963. Through historical analysis, this research examines the editorial and publication forces that guided Jack and Jill 's approach amid other contemporaneous children's magazines that did contain advertising. While the findings recognize that the magazine's editors actively protected readers from commercial pressure, an examination of early issues of Jack and Jill identify that the magazine included previously unacknowledged adlike content throughout World War II that may have influenced young readers. The content, part of the U.S. Treasury's War Bonds and Stamps Drive, an agency-avowed advertising initiative, began with Jack and Jill 's involvement in the magazine industry's "United We Stand" campaign in July 1942 and was inserted intermittently through March 1945. The findings of this study demonstrate the value of historical research in understanding commercial influences on children and identify how definitions of advertising have evolved to accommodate nontraditional practices as media has advanced. This research also suggests that such nontraditional practices have existed and effectively engaged child audiences for more than half a century, despite not being formally recognized as advertising by the broader media and the general public.